DETERMINANTS OF KOREAN SENIORS' TRAVEL DESTINATION CHOICE ATTITUDES - SUNG-CHAE JUNG (ASEAN Journal on Hospitality and Tourism, 2008)
This study examines the factors that determine where Korean seniors choose to travel. Using iterated principal factor analysis with a varimax rotation analysis technique, five preference factors in choice oftravel destination were revealed: tourism environment, events, feeling, differentiation, and culture. Duncan's multiple range test was then applied to examine the relative preference level of each of these factors in determining destination choice. The results indicate that Korean seniors ' choice of travel destination varies between different sets of sociodemographic and travel characteristics. This information can be used by the tourist industry as a tool to aid decision making about tourism policy and marketing activities and to help determine priority of assignments aimed at improving tourist supply.